Skull Base Reconstruction Using a Temporoparietal Galeal Flap in Simultaneous Transnasal and Transcranial Surgery for the Prevention of Carotid Blowout Syndrome: A Report of 3 Cases - Iwami, Kenichiro; Fujii, Masazumi; Jinguji, Shinya; Kishida, Yugo; Watanabe, Tadashi; Oosuka, Koji; Saito, Kiyoshi (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Carotid blowout syndrome (CBS) is a rare complication that usually occurs after removal of head and neck tumors. Since transnasal skull base surgery allows a wide exposure of the ventral skull base, neurosurgeons should pay attention to prevent this devastating complication. We present, three cases involving exposure of the internal carotid artery (ICA) at the skull base during the simultaneous transnasal and transcranial approach.Case Description The first patient was a 69-year-old man with a recurrent chordoma. The exposed ICA was covered by an abdominal fat graft and nasoseptal flap, but he experienced CBS 2 months later and died. The second patient was a 66-year-old man with an intraosseous cavernous angioma of the petrous bone. The exposed ICA was covered by a temporoparietal galeal flap (TPGF), abdominal fat graft, and nasoseptal flap. The third patient was a 73-year-old man with skull base radiation necrosis and intracerebral abscess after proton beam therapy for orbital adenoid cystic carcinoma. The exposed ICA was covered by TPGF. The second and third patients' postoperative courses were uneventful.Conclusion Based on our experience, a nasoseptal flap alone may be insufficient to protect ICA. TPGF is therefore another available reconstruction option that may help prevent CBS.
Keywords: carotid blowout syndrome; internal carotid artery; skull base reconstruction; temporoparietal galeal flap